Anxiety and depression related to yog nidra among professional students - Rupali Joshi (Wolters Kluwer Medknow Publications, 2020)
Background: Anxiety is one's response to stress. Its symptoms can be psychological, physical, or environmental challenges. Depression is a common mental disorder that presents with depressed mood, loss of interest or pleasure, feeling of guilt or low self-worth, disturbed sleep or appetite, low energy, and poor concentration. Yog nidra is probably the best known technique to induce complete physical and emotional relaxation. Aim: The aim of this study was to explore the effectiveness of yog nidra for reducing anxiety and depression among first-year professional students. Materials and Methods: The level of anxiety was measured by using State, Trait, and Free-Floating Anxiety Scale developed by Tripathi and Rastogi (1986). The Hindi version of Beck Depression Inventory by Arora and Prashant (1988) was used to assess the depression level of participants. The study was conducted in three phases. In Phase-1 (preintervention), data were obtained from 201 students. In the Phase-2 (intervention phase), the participants were selected on the basis of high scores on the measures of anxiety and depression and divided into intervention (28 students) and non-intervention groups (30 students). The intervention group was given yog nidra training regularly for 5 weeks. Posttest was conducted after 5 weeks of the intervention. Results: The results showed a reduction in mean scores on the measures of anxiety and depression within the intervention group but not in the nonintervention group, which indicated the effectiveness of practicing yog nidra for reducing anxiety and depression and its positive effects among professional students. Conclusion: A dramatic effect of practicing yog nidra was observed among students for reducing anxiety and depression.